Direitos individuais homogêneos: aspectos materiais, processuais e sua natureza jurídica - Silva, Geocarlos Augusto Cavalcante da (2012)
This paper aims to address the collective right in Brazil, with emphasis on homogeneous individual rights. In order to achieve this purpose, it presents the legal structure of class action in Brazil, its substantive and procedural aspects: the dichotomy between interest and right; types of transindividual right, res judicata; standing; and other legal concepts. Moreover, it performs a specific analysis of the emergence of new rights from the transformation of society. It concludes that the homogeneous individual right, as a type of transindividual right characterized by a common origin, is not to be confused with pure individual right, being an autonomous subjective right